IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK MUHAMMADIYAH 5 PURWANTORO - Erwahyudin, Devid Dwi; Ulfah Hanifah; Fatricia Sayshi Hayva Shaden (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to explain the application of character education through Islamic Religious Education subjects at SMK Muhammadiyah 5 Purwantoro. The background of this study is the importance of character education in shaping students' personalities to be noble, religious, and responsible amid the moral challenges of today's youth. Islamic Religious Education plays an important role as a medium for instilling ethical and spiritual values in schools. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of teachers and students. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing to obtain an in-depth picture of character education practices in schools. The results show that Islamic Education teachers integrate the values of honesty, discipline, responsibility, and tolerance into the learning process, whether through role modeling, habit formation, or religious activities at school. Although character education is being implemented well, there are still obstacles such as the negative influence of the environment outside of school and a lack of supervision of students outside of school hours. Therefore, strong cooperation between schools, parents, and the community is needed to shape students' character in a comprehensive and sustainable manner.